The public effect of private sustainability reporting: evidence from incident-based engagement strategy - Semenova, Natalia (Journal of business ethics, 2023)
This study examines whether private information exchange between institutional investors and public companies in engagement dialogs on sustainability issues improves the publicly disclosed measurements of the target company’s financial and non-financial performance and transparency. It uses a unique dataset containing 326 private reports related to environmental, social, and anti-corruption recommendations to address material incidents among publicly traded MSCI World Index portfolio companies of Nordic institutional investors. The results indicate that target companies appear to have similar values with matched companies on sustainability performance and transparency ratings in the 3 years following the initiation of private reporting. Unexpected sustainability incidents are subsequently reflected in the next year’s fall in the market value of target companies relative to MSCI World Index. This paper provides empirical evidence for the legitimacy-based provision of private sustainability information used in a larger disclosure system of public companies.